Implementation of the compassion-based curriculum at Lazuardi Athaillah GCS - M. Muhajir; A. Arnidah; Farida Febriati (Inovasi Kurikulum, 2024)
The compassion-based curriculum in this study refers to a systematically planned learning experience as well as hidden curriculum practices aimed at transmitting compassionate values to students. It can take the form of standalone subjects, integration into the school's curriculum and programs, or through informal learning experiences via social interactions in school. The purpose of this research is to understand the implementation of a compassion-based curriculum at Lazuardi Athaillah Global Compassionate School (GCS) to assess its urgency in fostering students' love, sympathy, empathy, altruism, and anti-violence (non-aggression) attitudes. The research method used is qualitative with a phenomenological approach. Deep interview transcripts are analyzed using interpretative phenomenological analysis (IPA). The research results indicate that the implementation of the compassion-based curriculum at Lazuardi Athaillah is carried out by teaching 20 compassionate characters named Lazuardi 20 through character-building subjects, integrated into the Cambridge Curriculum and the National Curriculum, trained through special school programs and hidden curriculum practices. Overall, the implementation of the compassion-based curriculum is going well. Through the implementation of the compassion-based curriculum, students are taught to always love God, others, and themselves. They are also taught to be tolerant, help alleviate others' suffering, care for the environment, and reject violence. AbstrakKurikulum berbasis welas asih dalam penelitian ini mengacu pada pengalaman belajar yang direncanakan secara sistematis maupun melalui praktik kurikulum tersembunyi yang bertujuan mentransmisikan nilai-nilai welas asih kepada peserta didik. Bentuknya bisa berupa mata pelajaran yang berdiri sendiri, integrasi ke dalam kurikulum dan program sekolah, maupun berupa pengalaman belajar yang terjadi secara informal melalui interaksi sosial di sekolah. Tujuan penelitian ini adalah untuk memahami implementasi kurikulum berbasis welas asih di Lazuardi Athaillah Global Compassionate School (GCS) guna melihat urgensinya dalam menumbuhkan rasa cinta, simpati, empati, altruisme, dan sikap anti-kekerasan (non-agresi) peserta didik. Metode penelitian menggunakan kualitatif dengan pendekatan fenomenologi. Transkrip wawancara mendalam dianalisis dengan menggunakan interpretative phenomenological analysis (IPA). Hasil penelitian menunjukkan, implementasi kurikulum berbasis welas asih Lazuardi Athaillah dilaksanakan dengan mengajarkan 20 karakter welas asih bernama Lazuardi 20 melalui mata pelajaran character building, diintegrasikan ke dalam Kurikulum Cambridge dan Kurikulum Nasional, dilatih melalui program khusus sekolah dan praktik kurikulum tersembunyi. Secara keseluruhan, implementasi kurikulum berbasis welas asih berjalan dengan baik. Melalui implementasi kurikulum berbasis welas asih, peserta didik diajarkan untuk selalu mencintai Tuhan, orang lain, dan dirinya sendiri. Peserta didik juga diajarkan untuk toleran, membantu mengurangi penderitaan orang lain, peduli terhadap lingkungan, dan menolak kekerasan.Kata Kunci: implementasi kurikulum; pendidikan karakter; pendidikan moral; welas asih